'Your care and concern are my burden!': Accounting for the emic concepts of 'attentiveness' and 'empathy' in interpersonal relationships among Taiwanese females. (4th April 2017) - Chang, Wei-Lin; Fukushima, Saeko
Abstract : While the enactment of gendered identities has been a key focus in the field of sociolinguistics and im/politeness (e.g. Holmes, 1995; Lakoff, 1975; Mills, 2003), research specifically investigating females' emic understanding in relation to im/politeness has not been paid much attention. Building on prior work on 'attentiveness' (Fukushima, 2004, 2009, 2011, 2013, 2015; Fukushima & Haugh, 2014), this article aims to further examine the emic understandings and evaluations of 'attentiveness' and 'empathy' in relation to 'im/politeness' by female speakers of Mandarin Chinese. It is suggested that, although the concepts of attentiveness (zhoudao) and empathy (titie) are intrinsically polite, these two concepts are found to be discursively disputable through the emergence of the three folk notions, meddlesomeness (jipo), familiarity, and reciprocity in the course of metapragmatic interviews. These notions give rise to cultural nuances in the evaluations of im/politeness which are thus grounded in a particular language or culture.